Response to Critical Views of Phenomenology of Film - Shawn Loht (Film-Philosophy, 2024)
This article responds to critical views of John Rhym, Martin Rossouw, Ludo de Roo, and Annie Sandrussi on my 2017 book Phenomenology of Film: A Heideggerian Account of the Film Experience. The article also takes up positive footholds from the analyses of Chiara Quaranta and Jason Wirth. The main topics addressed include Martin Heidegger’s ontic-ontological distinction; the notion of film-as-philosophy; being-in-the-world read as being-in-the-film-world; and questions surrounding the facticity and identity of the film viewer.